Sign Language Translator And Tracking For Speech And Hearing Impaired Person With Cloud Storage - Mrs.M.Jamuna Rani Sowndharya Lakshmi N Sowmiya D K Sreenidhi M Srinidhi S (International Journal of Advanced Science and Technology, 2020)
Normally deaf-dumb people use sign language for communication, but they can’t normally interact with others . Due to which communications between mute-deaf and a standard person have always been a challenging task.